2009
DOI: 10.5007/2175-7925.2009v22n4p73
|View full text |Cite
|
Sign up to set email alerts
|

Métodos de semeadura empregados como critério de avaliação fenotípica em melhoramento de feijão

Abstract: http://dx.doi.org/10.5007/2175-7925.2009v22n4p73No melhoramento de plantas é de grande importância a obtenção de ganhos genéticos para um conjunto simultâneo de caracteres agrícolas. O objetivo deste trabalho foi obter estimativas dos coeficientes de correlação fenotípica e avaliar os desdobramentos destas correlações em efeitos diretos e indiretos em relação aos diferentes métodos de semeadura realizados. Foram avaliados oito caracteres de importância agronômica (ciclo vegetativo, estatura de planta, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
2
0
3
Order By: Relevance
“…The characteristic that contributed most to the increased grain yield in beans was the plant height (+0.34) and stem diameter (+0.34) in Joaçaba and the number of nodes (+0.64) and stem diameter (+0.48) in Lages. Similar results were found by Vale et al (2009) who also found a positive correlation between the yield, plant height and height of the first pod insertion. In contrast, Cabral et al (2011) found that the plant height and height of the first pod insertion did not present a correlation with the yield.…”
Section: Resultssupporting
confidence: 78%
“…The characteristic that contributed most to the increased grain yield in beans was the plant height (+0.34) and stem diameter (+0.34) in Joaçaba and the number of nodes (+0.64) and stem diameter (+0.48) in Lages. Similar results were found by Vale et al (2009) who also found a positive correlation between the yield, plant height and height of the first pod insertion. In contrast, Cabral et al (2011) found that the plant height and height of the first pod insertion did not present a correlation with the yield.…”
Section: Resultssupporting
confidence: 78%
“…Conseqüentemente a MMG contribui para aumento do REND, ratificando que quando se seleciona para maior MMG tem-se maior REND. Segundo Vale et al (2009) o efeito da competitividade entre as plantas dentro da linha parece ser de extrema importância para incrementar a expressão do efeito genotípico, em detrimento do efeito de ambiente. Na (Tabela 3) estão apresentados os valores do desdobramento das correlações fenotípicas para o município de Lages nos anos agrícolas 2006/07 e 2007/08.…”
Section: Methodsunclassified
“…A interação genótipo x ambiente também deve ser pesquisada. Segundo Vale et al (2009), o componente desta interação pode mostrar que uma planta vigorosa e produtiva, em determinado ambiente, pode não repetir o mesmo desempenho quando cultivada em outro ambiente.…”
Section: Introductionunclassified